Risk assessment when consuming drinking water treated with chlorine dioxide and risk management in EU countries and Ukraine to protect public health - O.V. Zorina; O.V. Surmasheva; O.O. Polka; Yе.О. Mavrykin (Medičnì Perspektivi)
The purpose of the work was to conduct a comparative scientific analysis of the main approaches to risk assessment and risk management to prevent the negative impact of drinking water on public health when treating it with chlorine dioxide in EU countries and Ukraine. The main risk to the population's health arising when consuming drinking water, is the risk of its microbiologicall contamination. Microbiological contamination of drinking water corresponds to a high risk, while the formation of disinfection byproducts in drinking water is an average risk. The regulatory documents of all EU countries take into account the requirements of Directive 2020/2184/EU regarding the content of chlorites and chlorates in drinking water when treating it with chlorine dioxide, while in Denmark, Slovakia, Hungary, Spain, and France, a risk-oriented approach to the safety of drinking water forced to introduce stricter standards for these indicators (as mandatory, recommended or those, which can be temporarily raised).The scientific analysis of the regulation of drinking water quality in the EU countries and Ukraine, as well as field studies on the safety and quality of drinking water at the Dnipro water station in the city of Kyiv, allowed to assess the risks of drinking water hazards and became the basis for raising the issue of revising or canceling the unscientific standard for chlorine dioxide in drinking water of the distribution network (≥0.1 mg/l), revising the strict standard for chlorites (≤0.2 mg/l), as well as control of drinking water quality by the content of chlorates following the requirements of European legislation. When appointing the organizers, executors, and decision-makers regarding risk assessment, similar approaches were implemented in various EU countries; in the documents of many countries, there are references to the relevant scientific institutions and the functions assigned to them. Under such conditions, the working programs of production control over drinking water quality and modernization plans can be adapted to the relevant water supply system and modern realities.